Study on the formation of alligator crack and edge crack in high silicon grain oriented electrical steel during cold rolling - Jain V.; Patra S.; Halder C.; Hasan S.M.; Ghosh A. (My University, 2025)
Production of a thin cold rolled sheet of high silicon electrical steel is industrially challenging as it is associated with the formation of different types of cracks. The present study investigates the role of microstructure, crystallographic texture, and analytical stress state on the formation of alligator crack and edge crack during cold rolling of Fe-3.78 wt. % Si electrical steel. Owing to high strain incompatibility, alligator crack initiates from shear bands, which develops during cold rolling. Furthermore, the large difference in Taylor factors of {111}?110»and {001}?110»oriented grains assisted the crack to follow the hot band interface. Stress analysis based on the finite element method indicates that minor tensile stress in the normal direction develops during the exit stage of cold rolling. This tensile stress has been found to be sufficient to cause cleavage fracture during the last step of alligatoring. The crack propagation is assisted by the large size and favorable orientation of θ-fiber (ND

?001?) textured grains. On the other hand, the finite element method-based analysis suggests that high tensile stress at the edges during steady state condition initiates the cleavage edge crack, which propagates inward along the transverse direction during the final exit stage. Intermediate annealing and hot band annealing were found to be effective in eliminating the formation of alligator crack and edge crack, respectively. © 2022 Author(s).